A Study of job satisfaction of Filipino nurses - Dizon, Adelaida C. (Howard University, 1983)
Absenteeism, turnover rate and work performance have been linked with job satisfaction. Filipino nurses continue to serve as a vital source of manpower for the U.S. health care delivery system. Knowledge of job satisfaction is essential in determining strategies for promoting retention, decreasing absenteeism, and increasing work performance. Because little research had been reported on job satisfaction of Filipino nurses, this descriptive study explored job satisfaction with the following objectives ...